Treatment history and placebo responses to experimental and clinical pain in chronic pain patients. (7th April 2016) - Müller, M.; Kamping, S.; Benrath, J.; Skowronek, H.; Schmitz, J.; Klinger, R.; Flor, H.
Abstract: Background: Placebo analgesia refers to the reduction in pain due to the administration of an inert treatment. It is induced by expectations of pain relief which are enhanced by learning mechanisms. In healthy humans, prior positive experiences enhance the placebo response. However, the effects of patients' prior experiences with treatment on placebo responses have not yet been examined. This study investigated how verbal information, learning and treatment history influence the magnitude of placebo analgesia in chronic pain. Methods: We administered a pharmacological placebo intervention in a sample of chronic pain patients ( n  = 49) who were seeking treatment in an outpatient pain clinic. Analyses were based on placebo responders. Results: We found that verbal information about a potent pain‐relieving effect of the intervention induced a large placebo analgesic response to both acute experimental ( F (1, 44) = 43.35, p  < 0.001) and chronic pain ( F (1, 44) = 37.72, p  < 0.001). However, the placebo responses to experimental and chronic pain were not significantly related ( r  = 0.012, p  = 0.95). An additional conditioning procedure did not significantly enhance placebo analgesia. Treatment history modulated the magnitude of the placebo response: patients with a more negative pain‐related treatment history reported significantly larger placebo responses to their own chronic pain ( τ  = 0.271, p  = 0.044). Conclusions: We could show that placebo responses to both acute and chronic pain are high in pain treatment settings and that treatment history modulates this effect. Different mechanisms might underlie placebo responses to acute and chronic pain. Our findings highlight the necessity of considering placebo responses and treatment history in the treatment of chronic pain. What does this study add?: Placebo analgesia following verbal information of potent pain relief is high in chronic pain patients in a clinical setting. It is modulated by treatment history. Different mechanisms might underlie placebo analgesia to acute and chronic pain.